1987
DOI: 10.1103/physrevlett.59.2299
|View full text |Cite
|
Sign up to set email alerts
|

Large-Larmor-radius interchange instability

Abstract: We observe linear and nonlinear features of a strong plasma-magnetic-field interchange RayleighTaylor instability in the limit of large ion Larmor radius. The instability undergoes rapid linear growth culminating in free-streaming flute tips.PACS numbers: 52.35. Gz, 52.35.Py, 52.50.Lp, 52.55.Lf Plasma expanding into a magnetic field can undergo Rayleigh-Taylor or interchange instability as the heavy fluid (plasma) is decelerated by the light fluid (magnetic field). 1>2 Direct observations of this instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(71 citation statements)
references
References 10 publications
6
64
1
Order By: Relevance
“…Limits of the cross-field width of plasmoids that can penetrate through polarization appear in the literature 45 , and large plasmoids have been seen to break up into smaller plasmoids in laboratory experiments 16 . It is therefore interesting to estimate the width of the plasmoids that are observed here.…”
Section: Plasmoid Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Limits of the cross-field width of plasmoids that can penetrate through polarization appear in the literature 45 , and large plasmoids have been seen to break up into smaller plasmoids in laboratory experiments 16 . It is therefore interesting to estimate the width of the plasmoids that are observed here.…”
Section: Plasmoid Sizementioning
confidence: 99%
“…Experimental studies showed that plasmoids can penetrate magnetic fields, while the relative change of the magnetic field, caused by the plasmoid, remains small even for large values of the kinetic beta β k = W K /(0.5µ 0 B 2 ) 14 . Experiments with laser produced plasmas have shown that wide plasmoids can break up into smaller plasmoids as they move across the field 16 , and this has been attributed to the Rayleigh-Taylor instability 17 . In active space experiments, where ion beams were injected in the ionosphere, both polarization fields and magnetic field-aligned electric fields were observed 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous laboratory experiments used magneticpinch plasmas (e.g. Paul et al 1967;Stamper and DeSilva 1968;Keilhacker et al 1969;Martone and Segre 1970;Mourenas et al 2003) or laser-produced plasmas (Tsuchimory et al 1968;Borovsky et al 1984;Ripin et al 1987;Dimonte and Wiley 1991;Ditmire et al 2000), creating the first test beds where observations and models could be compared. Although limited in size and duration at scales that allow for a detailed study of shock formation and particle acceleration, these pioneering experiments made a valuable progress in understanding various aspects of collisionless shock physics (see reviews in Drake 2000 andZakharov 2003).…”
Section: Scaled Laboratory Experiments and First Resultsmentioning
confidence: 99%
“…MHD waves with frequencies which are not necessarily smaller than the ion gyrofrequency w C i (EMIC waves) have been observed in astrophysical [ 11 and cometary plasmas [2], the polar cusp [3] as well as in laser-blowoff experiments [4]. As the amplitudes of these waves can be large [3] it may be of general interest to estend previous nonlinear theories for waves with frequencies with w < wCi to the frequency range where w can be comparable to, or even larger than, the ion gyrofrequency.…”
Section: Introductionmentioning
confidence: 99%